Heat stress in poultry: the role of nutritional supplements in alleviating heat stress and enhancing gut health in poultry - Olayiwola, Sammad F.; Adedokun, Sunday A. (Frontiers in Veterinary Science, 2025)
Globally, heat stress (HS) is a major concern in poultry farming, adversely impacting bird productivity, health, welfare, and economic returns. As climate change intensifies, the occurrence and severity of HS are anticipated to rise, posing greater risks to the poultry industry and the increasing demand for food. Birds respond to HS by exhibiting different mechanisms, including behavioral and physiological changes, to regulate their body temperature. In poultry, HS has been associated with reduced feed consumption, growth, feed efficiency, quantity and quality of eggs produced, meat quality, reproductive performance, impaired gut health, and increased mortality. Also, HS induces acid–base imbalance, causing both respiratory alkalosis and metabolic acidosis. During HS, birds pant to cool down and exhale excessive carbon dioxide, leading to a decrease in blood pH. Nutritional interventions have emerged as a viable strategy to mitigate HS effects, with various dietary supplements demonstrating efficacy in improving poultry resilience. Vitamins (A, C, D, and E), minerals (selenium, zinc, chromium, sodium, potassium, and chloride), fat, amino acids, electrolytes, and in ovo feeding have been revealed to boost thermotolerance, support growth, and improve feed efficiency of birds under HS conditions. This review integrates current literature on the impact of HS on poultry production and examines how nutritional supplements can help alleviate the effects of this environmental stressor in the avian species.